SELF-COMPASSION DAN QUARTER LIFE CRISIS: POTRET EMERGING ADULTHOOD DALAM BAYANG FATHERLESS - Popi Avati; Aryanis Novera (Journal of Innovation Research and Knowledge, 2026)
This study aims to determine the effect of self-compassion on quarter life crisis in emerging adulthood who experience fatherlessness in Jabodetabek. Self-compassion is an attitude of loving oneself which consists of the dimensions of self-kindness vs. self-judgment, common humanity vs. isolation, mindfulness vs. overidentification, which are protective factors when experiencing quarter life crisis. A total of 238 emerging adults experiencing fatherlessness in Jabodetabek were selected using purposive sampling. This quantitative study used the quarter-life crisis scale adapted by Zuhriyah (2021) from the theory of Robbin and Willner. The self-compassion scale was translated by Sugianto et al. (2020) based on Neff's theory. Simple linear regression analysis was used. The results of the study indicate that self-compassion does not significantly affect the quarter-life crisis in emerging adults experiencing fatherlessness in Jabodetabek (r = 0.468). Higher self-compassion actually increases the quarter-life crisis.